2020
DOI: 10.3390/ani10061039
|View full text |Cite
|
Sign up to set email alerts
|

Broiler Chicks’ Motivation for Different Wood Beddings and Amounts of Soiling

Abstract: In the wild, excreta soiled surroundings can attract predators and spread disease. Yet, farmers rear broiler chicks in large barns with stocking densities that prevent excreta segregation. To measure chicks’ motivation to access unsoiled bedding or soiled litter (collectively, substrates) we used 40 16-day-old broiler chicks who were divided into six two-compartment pens. The ‘home’ compartment (H) contained soiled wood shavings, while the ‘treatment’ compartment (T) contained either aspen wood shavings, pine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 60 publications
4
12
0
Order By: Relevance
“…Moreover, a smaller proportion of turkeys than expected pushed 40% to access FP, SP, TSP and NS, although this proportion was near to the expected value to access SP and NS. Hence, these findings agree with studies performed with laying hens [25,36] and broiler chickens [37] that found that Galliformes worked harder for feed than floor substrates. Additionally, selection for more muscle and faster growth rate [7] may mean that, similar to broilers [38], turkeys could have disrupted satiety mechanisms.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, a smaller proportion of turkeys than expected pushed 40% to access FP, SP, TSP and NS, although this proportion was near to the expected value to access SP and NS. Hence, these findings agree with studies performed with laying hens [25,36] and broiler chickens [37] that found that Galliformes worked harder for feed than floor substrates. Additionally, selection for more muscle and faster growth rate [7] may mean that, similar to broilers [38], turkeys could have disrupted satiety mechanisms.…”
Section: Discussionsupporting
confidence: 92%
“…Even when regularly fed, semi-wild junglefowl foraged for 61% of the time they spent active, as well as spent 34% of their time scratching, a behavior considered to be associated with foraging 34 . Without access to a preferred substrate or environment, domestic fowl forage in feces 35,36 , suggesting that this behavior is highly motivated. Commercial broilers can be deprived of all three of these high-motivation behaviors; they do not have access to perches or proper substrate to dustbathe and forage in.…”
mentioning
confidence: 99%
“…The effect of substrates on the behavior and preferences of other commercially farmed Galliformes such as pheasants, guinea fowl, Japanese quail, bobwhite quail, and turkeys is therefore unknown. Nevertheless, the stimulating and motivating qualities of substrates for dustbathing, pecking, and foraging is expected to be similar, if not the same, for other commercially relevant Galliformes (36,(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%